Type I interferon signalling is not required for the induction of endotoxin tolerance. (July 2017) - Karimi, Yalda; Poznanski, Sophie M.; Vahedi, Fatemeh; Chen, Branson; Chew, Marianne V.; Lee, Amanda J.; Ashkar, Ali A.
Highlights: Type I interferon signalling is not involved in the induction of LPS tolerance. Peritoneal macrophages from BL6 and IFNAR1 −/− mice are equally tolerized towards LPS. IFNAR1 −/− mice have increased survival post LPS challenge than BL6 mice. Abstract: Endotoxin, or LPS tolerance, is an immunomodulatory mechanism that results in a significantly diminished response to secondary LPS exposure, which may serve to protect the host against endotoxic shock. Type I interferons (IFNs) are cytokines released upon LPS binding to TLR4 and have been shown to have immunomodulatory properties. Due to this regulatory function of type I IFN, we aimed to investigate the role of type I IFN signalling in LPS tolerance. Our data suggests that type I IFN does not play a role in LPS tolerance in vitro, as both wild type and IFNAR1 −/− peritoneal macrophages showed reduced cytokine production after secondary LPS exposure. Furthermore, both wild type and IFNAR1 −/− mice were protected from a lethal dose of LPS after receiving three small doses to induce tolerance. However, IFNAR −/− mice seemed to recover faster than wild type mice, suggesting type I IFN signalling plays a detrimental role in LPS-induced sepsis. Although type I IFN may have a regulatory function in microbial infections, it does not seem to play a role in endotoxin tolerance. Type I IFN involvement in bacterial infection remains complex and further studies are needed to define the regulatory function of type I IFN signalling.